Gsm Encryption Algorithm Emulation Using Neuro-Identifire - Al Ubaidy, Mahmood Khalel Ibrahem (Al-Nahrain Journal of Science, 2018)
The security model of the Global System for Mobile Communication (GSM) relies on security through obscurity (STO). The later is a controversial principal in security engineering based on the premise that security of an element or function can ensure security of the whole product. STO assumption breaks one of the basic requirements of cryptographic system (Kerckhoff’s assumption), which states that the security of the cryptographic system should lies solely on the key, and the algorithm should be assumed as publicly available. In this research, security through obscurity, Kerckhoff’s assumption and GSM encryption algorithm (A5) will be discussed. The target unknown encryption algorithm (A5) is constructed using a black-box approach with neuro-identifier and a set of input and output data only. The constructed algorithm then is tested and compared with actual unknown algorithm. The experimental results of the research demonstrate nearly complete similarities between both algorithms, which prove that a GSM security model cannot be secure through obscuring algorithms.